2016
DOI: 10.1016/j.biopha.2016.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of IL-10 secretion by Treg cells in osteoarthritis is associated with a reduction in Tim-3 expression

Abstract: Knee osteoarthritis (OA) is the most common cause of musculoskeletal pain and disability in the knee. Though traditionally thought a mechanical wear-and-tear disease, in recent years, knee OA as a low-grade, chronic inflammatory disease has been increasingly recognized. In this study, we examined the Treg responses in non-obese knee OA patients at different stages. Significantly elevated frequencies of CD4(+)CD25(+)Foxp3(+) Tregs were found in OA patients, while on the other hand, lower IL-10 secretion from Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 42 publications
3
26
2
Order By: Relevance
“…The destruction of bone and cartilage gives rises to a state of chronic inflammation [5] and is consistent with the finding of a smaller population of differentiated regulatory T (Treg) cells in the synovial membranes of OA vs. RA patients [6]. Interleukin (IL)-10 expression by Treg cells is also reduced in OA patients [7] whereas levels of helper T (Th) 17 cells in their joints are increased [8]. This imbalance of Th17/Treg, and therefore of pro-and antiinflammatory cytokines, may contribute to the pathogenesis of OA.…”
Section: Introductionsupporting
confidence: 72%
“…The destruction of bone and cartilage gives rises to a state of chronic inflammation [5] and is consistent with the finding of a smaller population of differentiated regulatory T (Treg) cells in the synovial membranes of OA vs. RA patients [6]. Interleukin (IL)-10 expression by Treg cells is also reduced in OA patients [7] whereas levels of helper T (Th) 17 cells in their joints are increased [8]. This imbalance of Th17/Treg, and therefore of pro-and antiinflammatory cytokines, may contribute to the pathogenesis of OA.…”
Section: Introductionsupporting
confidence: 72%
“…Indeed, Ponchel et al (11) analyzed blood from 121 healthy controls and 114 OA patients and found that the OA patients had fewer Treg cells than the healthy controls after adjusting for age (11). Although the frequency of CD4 + CD25 + Foxp3 + Treg cells has been found to be elevated in the blood of OA patients, OA patients show lower IL-10 secretion from Treg cells and fewer Tim-3 + Treg cells in the blood (78). Similarly, in a rat model of OA induced by the injection of papain and l -cysteine into the right knee joint, the percentage of CD4 + CD25 + Foxp3 + Treg cells in the peripheral blood was significantly lower in the OA rats than in the control rats (68).…”
Section: T Cells and Oamentioning
confidence: 99%
“…Surprisingly, CD4 þ Treg cells percentage decreased after the cycle of mud therapy in OA patients. There have been previous observations of raised levels of circulating CD4 þ Treg cells in OA [42][43][44], but paradoxically, despite elevated numbers of these cells, inflammation is still present in this pathology. This can be understood as an attempt of the immune system to control the inflammatory responses, but the persistence of inflammation could indicate that these cells present functional impairment that limits their capacity to suppress ongoing disease, perhaps due to an inhibition of their suppressive functions by proinflammatory cytokines or because of an increased number of activated effector T cells [44,45].…”
Section: Discussionmentioning
confidence: 84%